On 210Po and 210Pb in algae diet supplements — The assessed radiation hazard of aquatic superfoods. (March 2023) - Zhang, D.; Niemczyk, A.; Moniakowska, A.; Block, K.; Olszewski, G.; Strumińska-Parulska, D.
Abstract: Algae are believed to give health benefits. However, the studies showed they contain toxic elements, including radionuclides, and may affect human health. The study presents the values of activity concentrations of 210 Po and 210 Pb in the algae supplements available worldwide for adults. The activity concentrations (Bq/kg dw) ranged from 0.07 to 14.5 ( 210 Po) and from 0.06 to 8.48 ( 210 Pb). Also, the effective radiation doses and the cancer risk from 210 Po and 210 Pb decay ingested with analyzed algal supplements have been assessed. The highest values of annual effective doses have been estimated for 210 Po in the recommended portion of Spirulina ( Arthrospira platensis ) from China (59.7 μSv/year) and Diatomaceous earth from the USA (50.4 μSv/year). The cancer morbidity and mortality risk ranged from 10 −4 to 10 −8 . The study indicated the activity concentrations of 210 Po and 210 Pb were low, and algae supplements for human consumption could be considered safe food. Graphical abstract: Unlabelled Image Highlights: 210 Po and 210 Pb are present in algae supplements Wild-growing Ch. vulgaris contained more 210 Po and 210 Po than aquafarmed The highest annual doses from 210 Po decay would come from Chinese A. platensis and diatomite from the USA Algal superfoods can be considered safe